One‐Dimensional Nanostructured Pseudocapacitive Materials: Design, Synthesis and Applications in Supercapacitors. Issue 10 (2nd July 2019) - Sun, Jinfeng; Guo, Lingzhi; Sun, Xuan; Zhang, Jinyang; Hou, Linrui; Li, Li; Yang, Shuhua; Yuan, Changzhou
Abstract: In the past decades, pseudocapacitive materials (PCMs) for electrochemical energy storage have drawn enthusiastic attention from researchers, owing to their virtue of larger Faradaic capacitance facilitating enhanced energy densities compared to electric double‐layer capacitive materials. To maximize capacitive properties without sacrificing power densities, novel design and fine fabrication of innovative PCMs with rational micro‐structures become of significant importance. Typically, enormous efforts have been devoted to fabricating 1D nanostructured PCMs for advanced supercapacitors, thanks to their geometrical merits facilitating the ionic/electronic transport. This review mainly focuses on the latest development and progress of 1D nanostructured PCMs for advanced supercapacitors. Firstly, typical pseudocapacitive mechanisms are discussed in detail. Secondly, physicochemical properties and intrinsic merits of 1D nanoscaled electrodes are comprehensively described. Thirdly, representative synthetic methodologies, optimization strategies and involved formation mechanisms for 1D nanodimensional PCMs are surveyed. Besides, the applications of 1D versatile PCMs including 1D conventional nanostructures, nano‐arrays, core‐shell nano‐architectures and secondary superstructures are systematically summarized as competitive electrodes for supercapacitors. Finally, future challenges, prospects and opportunities of 1D nanostructured PCMs for next‐generation supercapacitors are further proposed. Abstract : There can be only one : the recent progresses in rational design and controllable synthesis of 1D nanostructured pseudocapacitive materials and their applications in advanced systems for electrochemical energy storage is summarized and an in‐depth understanding of pseudocapacitive mechanisms is provided. Furthermore, future challenges, prospects and opportunities of 1D nanostructured pseudocapacitive materials for next‐generation supercapacitors are emphasized.